2019
DOI: 10.16970/entoted.621304
|View full text |Cite
|
Sign up to set email alerts
|

Development of methodology for resistance screening of chickpea genotypes collected in Turkey to the root lesion nematode, Pratylenchus thornei Sher & Allen, 1953 (Tylenchida: Pratylenchidae)

Abstract: The root lesion nematode, Pratylenchus thornei Sher & Allen, 1953 (Tylenchida: Pratylenchidae) are considered economically important plant parasitic nematodes affecting chickpea [Cicer arietinum L. (Fabales: Fabaceae)] production. A major strategy to develop resistance to root lesion nematodes in chickpea is to assess and exploit their natural variation. Therefore, nine accessions of wild Cicer reticulatum Ladiz. (Fabales: Fabaceae), Cicer echinospermum P.H.Davis (Fabales: Fabaceae) and domesticate C. arietinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…According to the results, there was a significant difference between nematode species in the root sample, and population density of nematodes differed between cultivars of C. echinospermum and C. reticulatum studied. Behmand et al (2020) indicated that the population density of root lesion nematodes was differed with species (P. neglectus and P. thornei) and Cicer species. The population density of P. thornei in C. echinospermum was higher than the population density in C. reticulatum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results, there was a significant difference between nematode species in the root sample, and population density of nematodes differed between cultivars of C. echinospermum and C. reticulatum studied. Behmand et al (2020) indicated that the population density of root lesion nematodes was differed with species (P. neglectus and P. thornei) and Cicer species. The population density of P. thornei in C. echinospermum was higher than the population density in C. reticulatum.…”
Section: Resultsmentioning
confidence: 99%
“…One week after sowing, the seedlings were inoculated with number of 225 nematodes consisting of mixed development stages in 1 ml of water (Behmand et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation